Water Quality of Ebony Lakes in Bukit Golf Mediterania, Pantai Indah Kapuk, North Jakarta: Kualitas Air Danau Ebony di Kawasan Bukit Golf Mediterania, Pantai Indah Kapuk, Jakarta Utara - Syarif, Nawas; Hariyadi, Sigid; Krisanti, Majariana (Habitus Aquatica, 2024)
Ebony Lakes is an artificial lake that used as flood control and as an aesthetic function to raise the aesthetic value of the residential. The study was conducted for the purpose of proving that the operational management of the Lake Ebony improve the water quality of the lake. This research was conducted from March 2014-February 2015. Analysis method used in this research is the Pollution Index and STORET Index. Ebony lake contamination levels based STORET Index on the surface and the bottom water with the value range from -40 to -52. Pollution index values that was obtained from the surface and the bottom waters of Ebony Lake range from 1.54 to 10.26. Ebony polluted lake conditions was seen from parameters that was exceeded the quality standards class III PP no 82 tahun 2001, such as COD, BOD5, nitrites, H2. Status Ebony Lake based on Pollution Index relatively lightly polluted to heavily polluted. Based on STORET Index Ebony Lake, water quality status indicates heavily polluted conditions at each station with a higher trend in dry season than the wet season.